2019
DOI: 10.1073/pnas.1901974116
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of PNPLA3 on lipid droplets is the basis of associated hepatic steatosis

Abstract: Fatty liver disease (FLD) is a disorder in which accumulation of triglycerides (TGs) in the liver can lead to inflammation, fibrosis, and cirrhosis. Previously, we identified a variant (I148M) in patatin-like phospholipase domain-containing protein 3 (PNPLA3) that is strongly associated with FLD, but the mechanistic basis for the association remains elusive. Although PNPLA3 has TG hydrolase activity in vitro, inactivation or overexpression of the WT protein in mice does not cause steatosis. In contrast, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
199
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 46 publications
(60 reference statements)
12
199
1
4
Order By: Relevance
“…The most strongly associated genetic variant with NASH is a single‐nucleotide polymorphism (I148M) in the patatin‐like phospholipase domain‐containing protein 3 ( PNPLA3 ) gene, which encodes a lipid droplet protein and is involved at this lipolytic step. I148M variant PNPLA3 is degradation resistant, accumulates on lipid droplets, and is sufficient to induce steatosis . Hydroxysteroid 17β‐dehydrogenase 13 (HSD17B13), another lipid droplet protein, is up‐regulated in NASH .…”
Section: Steatosis and Lipotoxicitymentioning
confidence: 99%
“…The most strongly associated genetic variant with NASH is a single‐nucleotide polymorphism (I148M) in the patatin‐like phospholipase domain‐containing protein 3 ( PNPLA3 ) gene, which encodes a lipid droplet protein and is involved at this lipolytic step. I148M variant PNPLA3 is degradation resistant, accumulates on lipid droplets, and is sufficient to induce steatosis . Hydroxysteroid 17β‐dehydrogenase 13 (HSD17B13), another lipid droplet protein, is up‐regulated in NASH .…”
Section: Steatosis and Lipotoxicitymentioning
confidence: 99%
“…In brief, the role of HSD17B13 in human physiology and the molecular mechanism behind the genetic protection are far from being clear. The interplay between HSD17B13 and PNPLA3 is a further complicating issue, especially given that PNPLA3 itself is a potential target for therapeutic inhibition in the context of FLD . It will be important to determine what proportion of the protective effect of the HSD17B13 variant is mediated by PNPLA3 downregulation.…”
mentioning
confidence: 99%
“…Another study published recently highlights the importance of the I148M mutation on PNPLA3 turnover and protein abundance . The authors found that despite similar mRNA levels, the protein expression of the I148M variant is higher than wild type.…”
Section: Mechanism Debatedmentioning
confidence: 97%
“…Despite the importance of PNPLA3 I148M, the intrinsic pathogenic mechanisms underlying this variant have been unclear. However, several recent papers have provided new insights into the detailed molecular mechanism through which the I148M variant leads to steatosis …”
Section: Mechanism Debatedmentioning
confidence: 99%
See 1 more Smart Citation